Measuring the embryonic heart rate of wild birds: An opportunity to take the pulse on early development. (8th November 2017) - Sheldon, Elizabeth L.; McCowan, Luke S. C.; McDiarmid, Callum S.; Griffith, Simon C.
Abstract: Embryonic heart rates have the potential to provide great insight into physiological variation and ontogenic status in early development. The availability of a relatively inexpensive and portable piece of equipment, the Buddy digital egg monitor (Vetronic Services, Abbotskerswell, Devon, UK), provides an opportunity to measure embryonic heart rate noninvasively in the field. Here, we demonstrate the application of this equipment in the climatically harsh Australian outback. We characterize variation in embryonic heart rate in the Zebra Finch ( Taeniopygia guttata ) with respect to a range of abiotic and biotic variables. Heart rate increased throughout embryonic development and was positively correlated with ambient temperature. There was a strong effect of the nest of origin, but no clear effect of laying order or egg size, on embryonic heart rate. Our results demonstrate the sensitivity of embryonic heart rate to environmental conditions and/or natal origin. We review other studies that have used the digital egg monitor, and, in discussing our own results, identify areas of avian biology that could benefit from embryonic heart rate measurements in the future.